PAF antagonist protective effect on ischemic damage of contralateral testes in unilateral testes torsion - Orhan, Irfan; Hayit, Hüseyin; Duksal, Imed; Özercan, Ibrahim H.; Firdolaş, Fatih; Semercöz, Atilla (My University, 2004)
Introduction: Testicular torsion is a urological emergency that is rarely encountered but causes irreversible fertility changes if untreated. In the present study, the effectiveness of Ginkgo Biloba, a platelet activator factor (PAF) antagonist, was assessed in the prevention of ischemic injury in contralateral testis after left testicular torsion. Materials and Methods: A total of 24 male, adult Sprague Dawley rats were randomized into four groups each containing 6 rats. Group 1: control group, group 2: sham operated rats, group 3: left testicular torsion was performed for 6 hours, group 4: EGB-761 Ginkgo Biloba (0.3 mg/kg) was injected intramuscularly 30 minutes before the torsion. Right orchiectomy was performed to rats in all groups and the samples were examined in respect to macroscopic and histopathologic changes. Results: At the end of the experiment, both macroscopically and histopathologically no significant difference was detected between the testes of rats in all groups. In point of seminiferous tubule size there is no significant difference between group 1 and 2. When these two groups compared, one by one, with group 3 in which only ischemia is formed on the right testes we established an evident difference (for group 1 and 3 p<0.001 and for group 2 and 3 p<0.001). When we compared the seminiferous tubule size of the rats in group 4 and group 1 and 2 no significant difference is determined (for group 1 and 4 p>0.05). Furthermore, seminiferous tubule size changes formed because of the ischemia between group 3 and 4, in group 4 significantly fewer than group 3 (p<0.001). In point of edema there is no significant difference between group1 and 2. When these two groups compared one by one with group 3 in which only ischemia is formed on the right testes of the rats, an evident difference is determined (for group 1 and 3 p< 0.05, for group 2 and 3 p<0.05). When we compare the edema on the testes of the rats in group 1 and 2 with group 4, no difference determined (for group 1 and 4 p<0.05; for group 2 and 4 p<0.05). Also, edema formed the result of ischemia between group 3 and 4, in group 4 significantly fewer than group 3 (p<0.05). There is no significant difference about spermatogenetic activity, rupture of the tubule, germ cell changes, hemoragy and Leydig cell changes between the groups (p>0.05). Conclusion: It was determined that contralateral testicular ischemic injury induced by testicular torsion can be significantly decreased with the use of EGB-761 Ginkgo Biloba, a PAF antagonist.
Tek Tarafli Testis Torsiyonunda PAF Antagonistinin Karşi Taraf Testisin ? Iskemik Hasarindaki Koruyucu Etkinli?i
Keywords: Contralateral; EGB-761 ginkgo- biloba; Ischemia; Testicular torsion